All-fiber widely tunable mode-locked thulium-doped laser using a curvature multimode interference filter. (2nd June 2016) - Li, N; Liu, M Y; Gao, X J; Zhang, L; Jia, Z X; Feng, Y; Ohishi, Y; Qin, G S; Qin, W P
Abstract: We demonstrated a widely tunable mode-locked thulium doped fiber laser (TDFL) by using a homemade multimode interference filter (MMIF). The MMIF had a structure of single mode fiber (SMF)—multimode fiber (MMF)—SMF and three main transmission peaks at 1901.2, 1957.2 and 2043.2 nm. By mechanically bending the MMIF, the three main transmission peaks were tuned in the range of 1860–2024 nm due to multimode interference effect. By inserting the MMIF into a passively mode-locked TDFL cavity pumped by a 1570 nm fiber laser, a tunable mode-locked TDFL with a tuning range of 1919.6–2014.9 nm was achieved by adjusting the MMIF. To the best of our knowledge, such a tunable range is the largest among all-fiber tunable mode-locked TDFLs.